ANALISIS PENGARUH CUSTOMER EXPERIENCE TERHADAP MINAT BELI ULANG KONSUMEN PADA DRESS UP LAUNDRY & DRY CLEANING SERVICE CABANG BENHIL JAKARTA PUSAT - Agus Wahyono (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2017)
The purpose of this research is to know the influence of Customer Experience against the interests of consumers on the anniversary of buy Dress Up Laundry & Dry Cleaning Service data collected using the formula slovin with spread 100 respondents customer Dress Up Laundry Dry Cleaning Service & methodology this research is quantitative analysis performed with the associative analysis of multiple linear regression. The results showed partially sense experience is a positive and significant effect against the interest to buy, feel the experience positive and significant effect against the interest to buy, think positive and influential experience significantly to buy interest, act experience positive and significant effect against the interest to buy, relate the experience positive and significant effect against interest buy. simultaneous sense, feel, think, act, relate together in the same positive and significant effect of 75.3% and the remaining 24.7% influenced by other variables that are not described in This research.